함정 전투체계의 도메인 컴포넌트 참조 아키텍처 - 이선열(Seonyeol Lee); 채흥석(Heung-Seok Chae) (한국정보통신학회논문지, 2019)
The naval combat system is gradually evolving, actively accepting technological advances. The domain components of the naval combat system must also be adapted to the gradual evolution of the naval battle system. In other words, domain components should be easy to change. However, existing domain components do not fully consider changeability. In particular, when receiving more messages than planned from the middleware, it does not consider a way to process them in a timely manner. We propose a domain component reference architecture for timely processing of increased messages. The proposed architecture separates domain components so that business logic can operate independently, and sets up multiple business logic to operate simultaneously to handle increased messages. The track management domain component is designed using the proposed reference architecture to confirm the applicability. 함정 전투체계는 기술의 발전을 적극적으로 수용하여 점진적으로 진화하고 있다. 함정 전투체계의 도메인 컴포넌트들 또한 함정 전투체계의 점진적 진화에 맞추어 변경되어야 한다. 즉, 도메인 컴포넌트는 변경용이성을 가져야 한다. 그러나 기존 도메인 컴포넌트는 변경용이성을 충분히 고려하지 않는다. 특히, 미들웨어로부터 계획된 것보다 더 많은 메시지를 수신할 경우, 이에 대응하기 위한 방안을 고려하지 않는다. 우리는 증가된 메시지에 신속하게 대응할 수 있는 도메인 컴포넌트 참조 아키텍처를 제안한다. 제안된 아키텍처는 비즈니스 로직이 독립적으로 동작할 수 있도록 도메인 컴포넌트를 분리하고, 다수의 비즈니스 로직이 동시에 동작하도록 설정하여 증가된 메시지를 처리하고자 한다. 제안된 참조 아키텍처를 이용하여 표적관리 도메인 컴포넌트를 설계하여 참조 아키텍처의 적용 가능성을 확인하였다.